‘A field of divine activity’ Divine aseity and holy scripture in dialogue with John Webster and Karl Barth - Rempel, Brent A. (2020)
In dialogue with John Webster and Karl Barth, this essay considers the intersection of divine aseity and holy scripture. I argue that the doctrine of holy scripture is constituted by a backward reference, namely, the plentiful life of the triune God. The doctrine of divine aseity denotes God's self-existent triune life, which anchors God's bestowal of life. Construed negatively, aseity establishes the incommensurability of God and creatures by distinguishing, without sundering, scripture and God's self-communicative presence. Construed positively, aseity constitutes scripture as ‘a field of divine activity’, the sphere of the life-giving missions of the Word and Spirit. The triune God who lives a se, elects the texts of scripture to serve as intermediaries of God's vivifying address.
Keywords: John Webster; Karl Barth; Trinity; Aseity; Holy Scripture